2011
DOI: 10.1387/ijdb.103226ia
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of lymphangiogenesis in development and cancer

Abstract: The lymphatic system, also named the second vascular system, plays a critical role in tissue homeostasis and immunosurveillance. The past two decades of intensive research have led to the identification and detailed understanding of many molecular players and mechanisms regulating the formation of the lymphatic vasculature during embryonic development. Furthermore, clinical and experimental data clearly demonstrate that the formation of new lymphatic vessels by sprouting lymphangiogenesis from pre-existing lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 133 publications
0
52
0
1
Order By: Relevance
“…Similar to tumor angiogenesis, lymphangiogenesis is mainly influenced by the tumor microenvironment (3). Among a variety of factors, VEGF-C and VEGF-D are considered the key drivers of lymphangiogenesis (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to tumor angiogenesis, lymphangiogenesis is mainly influenced by the tumor microenvironment (3). Among a variety of factors, VEGF-C and VEGF-D are considered the key drivers of lymphangiogenesis (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…PROX1 knockdown decreased the expression of lymphangiogenic inducers VEGF-C, VEGF-D, and COX-2 in human gastric cancer cells. Previous studies have shown that VEGF-C and VEGF-D induce the proliferation and migration of LECs by activating VEGFR-3, and that overexpression of VEGF-C, VEGF-D, or VEGFR-3 is associated with lymphatic metastasis and poor clinical outcomes of various cancers [25][26][27]. Further, COX-2 promotes tumor lymphangiogenesis and lymph node metastasis [28].…”
Section: Discussionmentioning
confidence: 99%
“…The aorta (ao) and pulmonary artery (pa) are indicated at a low magnification (A, 100x) and higher magnifications are in (B, 200x) and (C, 400x) (Barbosky et al, 2006). (Albrecht and Christofori, 2011;Schulte-Merker, 2011;Witte et al, 2011). Transgenic mice have been created and markers for lymphatics have been identified that have made the study of lymphatic development much more accessible.…”
Section: Where Do Endothelial Cells In the Heart Come From?mentioning
confidence: 99%